Plant phosphoinositide signaling - dynamics on demand - Heilmann, Ingo (Biochimica et biophysica acta, 2016)
Eukaryotic membranes contain small amounts of lipids with regulatory roles. An important class of such regulatory lipids are phosphoinositides (PIs). Within membranes, PIs serve as recruitment signals, as regulators of membrane protein function or as precursors for second messenger production, thereby influencing a multitude of cellular processes with key importance for plant function and development. Plant PIs occur locally and transiently within membrane microdomains, and their abundance is strictly controlled. To understand the functions of the plant PI-network it is important to understand not only downstream PI-effects, but also to identify and characterize factors contributing to dynamic PI formation. This article is part of a Special Issue entitled: Plant Lipid Biology edited by Kent D. Chapman and Ivo Feussner. •Plant phosphoinositides (PIs) are subject to dynamic control.•A dynamic balance of biosynthesis and degradation of PIs can be rapidly perturbed.•The subcellular distribution of plant PIs can be dynamic.•Key steps of plant PI-metabolism might be regulated at the post-translational level.•There is little evidence for rapid transcriptional control of plant PI-metabolism.